Effect of hospital pharmacist counseling on clinical outcomes of type 2 diabetes mellitus outpatients - Wiwiet Nurwidya Hening; Ratu Ayu Dewi Sartika; Rani Sauriasari (Wolters Kluwer Medknow Publications, 2019)
Objective: In Indonesia, the role of a hospital pharmacist in pharmaceutical care is still limited or even absent. This study aimed to determine whether counseling by a pharmacist could improve medication adherence, controlling the glycemic status, lipid profile, and blood pressure of type 2 diabetes mellitus (T2DM) outpatients. Methods: We conducted an interventional study at RSUD Kota Depok, a secondary public hospital, Indonesia, from April to October 2018. Counseling was given three times during the 4-month study. The study design was quasi-experimental with pretest-posttest group design on 77 respondents divided into intervention group (IGs) (n = 39 people) who received counseling and booklets from the hospital pharmacist and control group (CG) (n = 38 people) who were only given the booklets. We measured adherence with the Medication Adherence Questionnaire and conducted blood tests for fasting blood glucose (FBG), postprandial blood glucose (PPBG), glycosylated hemoglobin A1, lipid profiles (total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, and TG), and blood pressure measurements. Findings: In the IG, adherence parameters such as HbA1c and lipid profile improved, whereas in the CG, there were no statistically significant changes in clinical parameters and even nonadherence score increased (P = 0.008). IG showed statistically significant improvement in medication adherence, in parameters such as FBG, PPBG, and HbA1c, compared to CG. Based on the Chi-square test, IG also showed a statistically significant improvement in the number of controlled FBG (P = 0.05) and HbA1c (P < 0.001) compared to CG. In addition, a multivariate analysis showed that counseling by hospital pharmacist was 2.764 times (95% confidence interval [CI]: 1.096-6.794) and 9.964 times (95% CI: 3.434-28.917) better than no counseling in improvement of FBG and HbA1c, respectively. However, the significance disappeared after adjusted by type of medicine, duration of diabetes mellitus drug use, and medication adherence. Conclusion: Hospital pharmacist counseling is an important and significant factor in improving FBG and HbA1c levels of T2DM outpatients.